Implementasi Manajemen Strategik dalam Pertunjukan Ramayana Prambanan - Cahyani Tunggal Sari (Greget, 2010)
This study examines the strategic management, in the form of an environmental analysis, of the Ramayana Ballet at Prambanan. Specifically, it examines the strengths and weaknesses of the internal environment, and the opportunities and threats of the external environment of the Ramayana Ballet at Prambanan in its capacity as a business. An environmental analysis is needed in  order to anticipate the old strategies that may undergo changes in the rapid onset and high intensity of globalization. The correction of these strategies may influence the company’s vision and mission.     Keywords:  Environment analysis and strategic management